Math, asked by guptabablu41586, 4 months ago


The sum of two integers is -11 and their product is -80. What are the two integers?

Answers

Answered by 12thpáìn
164

Given

  • Sum of two integers = (-11)
  • Product of two integer= (-80)

To Find

  • The two integers

Let the Two integers be x and y

then

  •  \sf \: x+y= -11 \:  \:  \:  \:  \:  \:  -  -  -  -  - (1)
  •  \sf \: x× y= -80 \:  \:  \:  \:  \:  \: -  -  -  -   - (2)\\

we know that

  •  \boxed{ \bf{ {(a  -  b) }^{2} =  {a}^{2}   + {b}^{2}   - 2ab}}

{~~~~~:~~\implies \sf (x - y) ^{2}  =  {x}^{2}  +  {y}^{2}   -2 xy}

  •  \boxed{ \bf{ {a}^{2}  +  {b}^{2}  ={ (a + b)}^{2}  - 2ab}}

{~~~~~:~~\implies \sf (x - y) ^{2}  =  \{{ (x + y)  }^{2}  - 2xy  \} -2 xy}

  • Putting ( x+y) =-11 and xy= -80

{~~~~~:~~\implies \sf (x - y) ^{2}  =  { (- 11)  }^{2}  - 2 \times ( - 80)   -2 \times ( - 80)}

{~~~~~:~~\implies \sf (x - y) ^{2}  = 121   + 160 + 160}

{~~~~~:~~\implies \sf (x - y) ^{2}  = 121   + 320}

{~~~~~:~~\implies \sf (x - y) ^{2}  = 441}

{~~~~~:~~\implies \sf x - y   = \sqrt{441} }

{~~~~~:~~\implies \sf x - y  = \sqrt{3 \times 3 \times 7 \times 7} }

{~~~~~:~~\implies \sf x - y  = \sqrt{21 \times 21} }

{~~~~~:~~\implies \sf x - y  = \sqrt{  {21}^{2}  } }

{~~~~~:~~\implies \sf x - y  = 21   \:  \:  \:  \:  \:  \:  -  -  -  - (3)} \\  \\  \\

Now,

  •  \sf \: x - y = 21 \:  \:  \:  \:  \:  \:  -  -  -  - (3)
  •  \sf{x + y =  - 11} \:  \:  \:  \:  \:  \:  -  -  -  - (1)

  • On adding Both Equation y term Cancel

{~~~~~:~~\implies \sf 2x+y-y =  21  - 11}

{~~~~~:~~\implies \sf 2x\cancel{+y}\cancel{-y} =  21  - 11}

{~~~~~:~~\implies \sf 2x =  21  - 11}

{~~~~~:~~\implies \sf 2x =  10}

{~~~~~:~~\implies \sf x = 5}

Putting x= 5 in Equation 1

{~~~~~:~~\implies \sf x + y =   - 11}

{~~~~~:~~\implies \sf  5+ y =   - 11}

{~~~~~:~~\implies \sf y =   - 11 - 5}

{~~~~~:~~\implies \sf y =   -16} \\  \\  \\  \\

  • Hance x= 5 and y = -16 .

Verification

\small\small\small\small\small \sf{ \:  \:  \: \pink{x + y =  - 11} ~~~~~~~~~~~\:  \:  \:  \:  \: or\green{= \:  \:  \:  \:  \: xy =  - 80}}

\small\small\small\small\small\small\small\sf{ \:  \:  \:\pink{ 5 +( - 16) =  - 11}} \:  \:  \:  \:  \: or \:  \:  \:  \:  \:\green{ 5 \times ( - 16)=  - 80}

\small\small\small\small\small\small\small{ \:  \:  \:  \pink{ -  11 =  - 11\:  \:  \: _{_{_{ verifed}}}} \:  \:  \:  \:  \: or \:  \:  \:  \:  \:  \green{- 80=  - 80 \:  \:  \: _{_{_{ verifed}}}}}\\\\

\begin{gathered}\begin{gathered}\\\\\begin{gathered}\begin{gathered}\begin{gathered}\begin{gathered} \bigstar \: \underline{\sf{\red{Happy~ Studying}}\bigstar}\\ {\boxed{\begin{array}{cc}\dashrightarrow \sf(a + b)^{2} = {a}^{2} + {b}^{2} + 2ab \\\dashrightarrow \sf(a - b)^{2} = {a}^{2} + {b}^{2} - 2ab \\\dashrightarrow \sf(a + b)(a - b) = {a}^{2} - {b}^{2} \\\dashrightarrow \sf(a + b) ^{3} = {a}^{3} + b^{3} + 3ab(a + b) \\ \dashrightarrow\sf(a - b) ^{3} = {a}^{3} - b^{3} - 3ab(a - b) \\ \dashrightarrow\sf a ^{3} + {b}^{3} = (a + b)(a ^{2} + {b}^{2} - ab) \\\dashrightarrow \sf a ^{3} - {b}^{3} = (a - b)(a ^{2} + {b}^{2} + ab \\\dashrightarrow \sf{a²+b²=(a+b)²-2ab}\\ \end{array}}}\end{gathered}\end{gathered}\end{gathered}\end{gathered}\end{gathered}\end{gathered}

Similar questions